2022
DOI: 10.3390/jcm11144096
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Long-Term Proton Pump Inhibitor Use on Cardiovascular Health: A Meta-Analysis

Abstract: Introduction: Proton pump inhibitors (PPIs) are one of the most prescribed classes of drugs worldwide as a first-line treatment of acid-related disorders. Although adverse effects are rare and rapidly reversible after a short exposure, concerns have been recently raised about a greater toxicity on cardiovascular health after a longer exposure, especially when combined with clopidogrel. We aimed to evaluate the safety of long-term PPI use on cardiovascular health in patients with known atheromatous cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Additionally, a meta-analysis of six randomized controlled clinical trials, two post-hoc analysis, and two observational studies showed a positive correlation between the use of PPIs and the incidence of myocardial infarction and other cardiovascular issues. 54 …”
Section: Adverse Effects-associated With Long-term Ppi Therapymentioning
confidence: 99%
“…Additionally, a meta-analysis of six randomized controlled clinical trials, two post-hoc analysis, and two observational studies showed a positive correlation between the use of PPIs and the incidence of myocardial infarction and other cardiovascular issues. 54 …”
Section: Adverse Effects-associated With Long-term Ppi Therapymentioning
confidence: 99%
“…Jednak nie pozostawała ona istotna statystycznie dla ryzyka zawału mięśnia sercowego (p = 0,11). 70 Należy również pamiętać o zaburzeniach elektrolitowych pod postacią między innymi hipomagnezemii, do których powstania przyczynia się długotrwałe zażywanie IPP. Obniżony poziomu magnezu może wywołać wydłużony odstęp QT i następnie wystąpienie groźnego dla życia torsade de pointes.…”
Section: Ipp a Choroba Sercowo-naczyniowaunclassified
“…The association between chronic PPI use and adverse effects, including increased cardiovascular and cerebrovascular risk, renal deterioration, and the onset of dementia, raises important questions regarding the longterm safety of these medications. While these associations have been noted in epidemiological studies, it is essential to acknowledge that causation has not been definitively established, and the precise mechanisms are still under investigation [3,4].…”
Section: Introductionmentioning
confidence: 99%